2015
DOI: 10.1007/s12028-015-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome: Complications, Outcomes, and Mortality

Abstract: In our large sample population-based study on NMS, we were able to identify the rates of several preselected complications and the mortality. The identification of independent mortality predictors in this study can guide physicians in the management and prognostication of this rare syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 17 publications
3
62
0
13
Order By: Relevance
“…In a study on 1,346 NMS patients, rhabdomyolysis was reported as the most prevalent complication (30.1%) compared to other associated complications 90. Electrolyte imbalances can cause serious cardiac arrhythmias that may end up in cardiac arrest if not treated promptly.…”
Section: How To Approach a Suspected Case Of Nmsmentioning
confidence: 99%
“…In a study on 1,346 NMS patients, rhabdomyolysis was reported as the most prevalent complication (30.1%) compared to other associated complications 90. Electrolyte imbalances can cause serious cardiac arrhythmias that may end up in cardiac arrest if not treated promptly.…”
Section: How To Approach a Suspected Case Of Nmsmentioning
confidence: 99%
“…Neuroleptic malignant syndrome (NMS) is an idiosyncratic reaction that can sometimes be life threatening can occur with metoclopramide and other DRBAs . The clinical triad consists of hyperthermia, rigidity, and alteration of mental status.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Our patient had improvement of fever and rigidity with dantrolene, but cardiorespiratory status continued to decline until he expired. Acute respiratory failure is the strongest independent predictor of mortality [13]. Other prognostic factors include acute renal failure, coexisting heart failure, and infections [5].…”
Section: Discussionmentioning
confidence: 99%